2015
DOI: 10.1242/jeb.115105
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal oscillation of vocal development associated with clustered singing by juvenile songbirds

Abstract: Spaced practice affects learning efficiency in humans and other animals. However, it is not well understood how spaced practice contributes to learning during development. Here, we show the behavioral significance of singing frequency in song development in a songbird, the zebra finch. Songbirds learn a complex song pattern by trial-and-error vocalizations as self-motivated practice, which is executed over a thousand times per day during the sensitive period of vocal learning. Notably, juveniles generate songs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…The change in the song motor pattern occurs primarily over intervals of sleep, and we have shown that adult song behavior also undergoes microscopic shifts in sleep. Our results may be related to a previous observation: as juveniles learn to sing, their songs progress through a day of practice 41 , but degrade slightly over intervals of sleep 42 . The depth of this overnight “backsliding” is positively correlated with the eventual success of song learning–indicating that nighttime song rearrangements are important for learning.…”
Section: Discussionsupporting
confidence: 88%
“…The change in the song motor pattern occurs primarily over intervals of sleep, and we have shown that adult song behavior also undergoes microscopic shifts in sleep. Our results may be related to a previous observation: as juveniles learn to sing, their songs progress through a day of practice 41 , but degrade slightly over intervals of sleep 42 . The depth of this overnight “backsliding” is positively correlated with the eventual success of song learning–indicating that nighttime song rearrangements are important for learning.…”
Section: Discussionsupporting
confidence: 88%
“…Singing prevention was highly effective: normal birds produce over 60,000 song bouts during the sensorimotor learning period (approximately 1,000 bouts/day × 60 days) [ 6 ], while the singing prevention birds produced less than 0.1% of this output (24–485 song bouts, mean = 279.0 bouts). When the birds were released from singing prevention at adulthood, they produced “age-unmatched” immature songs with highly variable acoustics and sequence of syllables, i.e., subsong or early plastic-like song ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…In a closed-ended vocal learner songbird, like the zebra finch, the time window of the sensorimotor learning phase lasts 2 months, beginning in juveniles at 30–45 post hatching day (phd) and ending in adulthood at 90–100 phd with the production of crystallized motif song patterns that are then maintained throughout life ( Fig 1A ). During the sensorimotor learning phase, zebra finches produce approximately 1,000 song renditions in a day through self-motivated vocal practice [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…To segregate potential effects of the song quality and cumulative singing amount on Arc expression, an experiment examining Arc expression in deafened juveniles during afternoon singing may be crucial. Diurnal syllable acoustic shift is significantly decreased in early‐deafened compared with intact juveniles (Ohgushi et al., ). Therefore, when early‐deafened juveniles freely sing until afternoon period, they accumulate total diurnal singing amount but their song quality is still highly variable due to no auditory feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile male zebra finches develop their song from highly variable vocalizations to achieve the stereotyped acoustic structures of adult crystallized song ( Figure 1a) (Immelmann, 1969;Price, 1979). Song acquisition is achieved through thousands of self-motivated singing utterances during the critical period of vocal learning (Johnson, Soderstrom, & Whitney, 2002;Ohgushi, Mori, & Wada, 2015). The acoustic features of song syllables are highly variable during the early plastic song phase (40-60 posthatching days [phd]), compared with those in the crystallized song produced at adulthood (Deregnaucourt et al, 2004;Wood, Osseward, Roseberry, & Perkel, 2013).…”
Section: Introductionmentioning
confidence: 99%